The impact of isotretinoin on platelet and white blood cell count in patient with acne vulgaris - Abdulwahab, Mayday Hadi; Alaa Abdul sahib Jawad (Karbala Journal of Medicine, 2023)
Background: Acne is a multifactorial disease and represents a spectrum of disease severity from a couple of blackheads and pustules to severe nodulocystic fulminant acne. The severity of the disease differs from patient to patient therefore Isotretinoin is a commonly used for treating acne. However, isotretinoin may lead to elevated serum levels of triglycerides and cholesterol, and it may affect liver function tests. Moreover, the effect of isotretinoin on hematological parameters remains controversial and examines changes in the blood chemistry panel, hematological parameters of patients diagnosed with acne and treated with isotretinoin. Methods: This comparative clinical trial carried out at Clinic in the Department of Dermatology in tow hospitals Salahaddin hospital and emergency hospital in Salahaddin city in Iraq. 116 patients were selected. Patients are suffering from acne and divided equally (58 patients each) to one of the two treatment regimens using isotretinoin and doxycycline. Group one was given oral isotretinoin twice daily for seven months and Group two was given doxycycline twice daily for same period. These patients were prepared before the time of study and were followed up during the treatment period. According to female, pregnancy prevented by two contraceptive methods. Both groups are investigated with the same investigations. Results: Among the 116 cases included in the study, (36) were male and (80) were female. The mean age of group one was 21.97±4.87 years and in group two was 21.72±4.95years Mean, platelet count increased, whereas white blood cell count decreased after isotretinoin treatment. But without any statically significant association. Conclusions: The results of this study revealed that no statically significant effect of white blood cells and platelets count after therapy by isotretinoin. Keywords: Acne, Isotretinoin, white blood cells and platelets. Aim of study The aim of this study was to assess and compare the efficacy of oral isotretinoin on WBC and platelet count in acne vulgaris patients.